Effect of aging, antioxidant, and mono- and divalent ions at high temperature on the rheology of new polyacrylamide-based co-polymers - Akbari, S. (MDPI AG, 2017)
The viscosity of four new polymers was investigated for the effect of aging at high temperature, with varying degrees of salinity and hardness. The four sulfonated based polyacrylamide co-polymers were FLOCOMB C7035; AN132 VHM; SUPERPUSHER SAV55; and THERMOASSOCIATIF copolymers. All polymer samples were aged at 80 °C for varying times (from zero to at least 90 days) with and without isobutyl alcohol (IBA) as an antioxidant. To see the effect of divalent ions on the polymer solution viscosity, parallel experiments were performed in a mixture of CaCl2-NaCl of the same ionic strength as 5 wt NaCl. The polymers without IBA showed severe viscosity reduction after aging for 90 days in both types of preparation (5 wt NaCl or CaCl2-NaCl). In the presence of IBA, viscosity was increased when aging time was increased for 5 wt NaCl. In CaCl2-NaCl, on the other hand, a viscosity reduction was observed as aging time was increased. This behavior was observed for all polymers except AN132 VHM. © 2017 by the authors. Licensee MDPI, Basel, Switzerland.